2015
DOI: 10.1038/ejhg.2015.178
|View full text |Cite
|
Sign up to set email alerts
|

The Koolen-de Vries syndrome: a phenotypic comparison of patients with a 17q21.31 microdeletion versus a KANSL1 sequence variant

Abstract: The Koolen-de Vries syndrome (KdVS; OMIM #610443), also known as the 17q21.31 microdeletion syndrome, is a clinically heterogeneous disorder characterised by (neonatal) hypotonia, developmental delay, moderate intellectual disability, and characteristic facial dysmorphism. Expressive language development is particularly impaired compared with receptive language or motor skills. Other frequently reported features include social and friendly behaviour, epilepsy, musculoskeletal anomalies, congenital heart defect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

12
151
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 123 publications
(164 citation statements)
references
References 37 publications
12
151
1
Order By: Relevance
“…Among patients aged ≤ 18 years, attention deficit/hyperactivity disorder (ADHD or autistic trait) are reported [Koolen et al, 2016]. A friendly/amiable attitude was described in the majority of adult (8/10) and pediatric patients [Koolen et al, 2016]. Regarding dysmorphic features, all adult patients with KdS showed a long face.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Among patients aged ≤ 18 years, attention deficit/hyperactivity disorder (ADHD or autistic trait) are reported [Koolen et al, 2016]. A friendly/amiable attitude was described in the majority of adult (8/10) and pediatric patients [Koolen et al, 2016]. Regarding dysmorphic features, all adult patients with KdS showed a long face.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, 7 adult patients (aged >18 years, range 20-50 years) are included in the series reported by Koolen et al [2016] and 2 young adults (23-and 31-years-old) are described in the cohort reported by Zollino et al [2015]. Clinical and molecular data of these patients are summarized in table 1 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations